Pendampingan Manajemen Operasional Serta Keuangan UMKM dalam Meningkatkan Kualitas Pelayanan pada Hotel Boegenville Lamongan : Pengabdian - Syahratul Aini; Azzikra Anugrah; Aditya Wahyu Ardiansyah; Rudi Wibowo (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting regional economic development, including in the hospitality service sector. However, in practice, hospitality MSMEs still face various challenges in operational and financial management. This paper presents the results of a community service activity based on Interprofessional Education (IPE), which aims to identify existing problems and provide mentoring support to Hotel Boegenville Syariah Lamongan in order to enhance its business competitiveness. The identified problems include the use of a manual financial recording system, the absence of written Standard Operating Procedures (SOPs), and unstructured employee workload and work scheduling. The implementation methods consisted of observation, interviews, training, and direct mentoring for the partner. The results indicate improvements in the organization of financial records through the adoption of a spreadsheet-based system, the development of SOPs as operational guidelines, and increased partner understanding in managing task distribution and employee working hours. This community service activity is expected to contribute to the sustainable improvement of operational and financial governance in hospitality MSMEs.